Retooling the 70/30 Grading Scheme for Practice-Based Art and Humanities Disciplines in Nigerian TVET Institutions: Expert Reflections - Olayemi Tosin Ajayi; Paul S. Seyi-Gbangbayau (Dampeng: Journal of Art, Heritage and Culture, 2026)
Assessment practices in Technical and Vocational Education and Training (TVET) institutions in Nigeria, especially within practice-based Art and Humanities disciplines, commonly rely on a 70/30 grading structure that allocates 70% to end-of-semester practical examinations and 30% to continuous assessment. While this system is institutionally entrenched, it often undervalues sustained studio engagement, progressive skill acquisition, and iterative creative experimentation throughout the semester. This study therefore investigates the effectiveness of internally redistributing the 70% practical component while retaining the official grading ratio, with the aim of improving fairness, student engagement, and authentic evaluation of practical competencies. The study is anchored in constructivist learning theory and authentic assessment principles, which emphasize continuous knowledge construction, reflective practice, and performance-based evaluation rather than single high-stakes examinations. A qualitative case-study methodology was adopted. Data were collected through semi-structured interviews, focus group discussions, classroom observations, and document analysis involving 216 students and 58 lecturers across nine practice-oriented departments following pilot implementation in 2016 and full institutional adoption in 2023. Findings reveal improved student attendance, stronger commitment to coursework, increased motivation toward studio practice, and better alignment between effort, skill development, and assessment outcomes. Lecturers reported enhanced monitoring of student progress, reduced last-minute academic pressure, and more reliable evaluation of creative competencies. The revised approach also fostered deeper engagement with practical tasks and collaborative learning processes. The study concludes that recalibrating internal assessment distribution within an existing grading framework can significantly enhance authenticity, fairness, and learning effectiveness without requiring major policy restructuring. It recommends broader institutional trials, policy dialogue among TVET stakeholders, lecturer capacity development in authentic assessment strategies, and further empirical studies to strengthen assessment practices in practice-based educational contexts.